Predominant yeasts in Chinese Dong fermented pork (Nanx Wudl) and their aroma-producing properties in fermented sausage condition - Ruifang Mi; Xi Chen; Suyue Xiong; Biao Qi; Jiapeng Li; Xiaoling Qiao; Wenhua Chen; Chao Qu; Shouwei Wang (Food Science and Human Wellness)
Yeasts are one of the predominant microbial groups in fermented meats. In this study, yeast communities of Chinese Dong fermented pork (Nanx Wudl) were investigated and the technological properties of 73 yeast isolates were evaluated. Through culture-dependent and high-throughput sequencing methods, the main yeast species identified included Pichia membranifaciens, Kazachstania bulderi, Millerozyma farinosa, Candida zeylanoides, Kazachstania exigua, Candida parapsilosis and Saccharomyces cerevisiae. Among these yeasts, P. membranifaciens, M. farinosa, K. exigua and K. bulderi were detected in fermented meats for the first time. A total of 73 yeast isolates was investigated for their lipolytic and proteolytic activities. All yeast species showed lipolytic activity, while proteolytic activity against meat protein was only detected in S. cerevisiae. Assay of aroma-producing potential was performed in a model simulating fermented sausage condition. Inoculation of yeast strains increased volatiles production, especially esters and alcohols. The highest ester production was observed in S. cerevisiae Y70 strain, followed by K. exigua Y12 and K. bulderi Y19. C. zeylanoides Y10 and S. cerevisiae Y70 were the highest producers of benzeneethanol and 3-methyl-1-butanol. S. cerevisiae Y70 with its highest production of branched alcohols and esters could be a promising candidate as aroma enhancer in the manufacture of fermented sausages.